Mapping the spatiality of the Indian Indigenous woman: figuration of Sarah Joseph’s Budhini as a nomadic subject - Raj, Mrinalini; Banerjee, Sarbani (AlterNative : an international journal of indigenous peoples, 2025)
This article aims to contribute to the larger discussion of the women of the Indian Indigenous communities in the gender discourse with a focus on the Santal (one of the largest Indigenous communities in India). It studies Sarah Joseph’s novel Budhini (2019/2021) based on the real-life story of Budhini, a Santal woman treated as an outcast by her community. It analyzes the figuration of an Indigenous woman as a nomadic subject in Indian society without her community. It explores how the position of an Indigenous woman is situated at the confluence of several strands of oppression through a reading of her usage of physical space reflecting her marginality. Reading the novel based on the framework of nomadic figuration and the discourse on space, it will analyze space as a medium of exercising power through exclusion, structuring the protagonist’s gendered identity in her struggles and oppression.